2022
DOI: 10.3390/buildings12070994
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Perception of Sustainability for Occupants of Residential Buildings: A Case Study in the UAE

Abstract: The residential sector is multi-faceted by nature. Although evidence shows that the UAE is among the countries in the world that take sustainability seriously, there is a lack of information about the perception of sustainability by occupants in the residential sector in the UAE. The aim of this paper is to assess the perception of sustainability of the residential sector in the UAE, which is achieved by following a methodological framework using the relevant literature review and experts’ knowledge. An online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 137 publications
0
1
0
Order By: Relevance
“…First, “Planning and Scheduling” is essential for measuring the efficiency and effectiveness of FM tasks organization and implementation, thus optimizing the use and allocation of resources. Also, given the UAE’s commitment to sustainability (Abuzaid et al. , 2022), experts revealed that “Waste Management” measure was crucially needed to be included since FM companies take recycling initiatives and waste minimization tactics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, “Planning and Scheduling” is essential for measuring the efficiency and effectiveness of FM tasks organization and implementation, thus optimizing the use and allocation of resources. Also, given the UAE’s commitment to sustainability (Abuzaid et al. , 2022), experts revealed that “Waste Management” measure was crucially needed to be included since FM companies take recycling initiatives and waste minimization tactics.…”
Section: Discussionmentioning
confidence: 99%
“…First, "Planning and Scheduling" is essential for measuring the efficiency and effectiveness of FM tasks organization and implementation, thus optimizing the use and allocation of resources. Also, given the UAE's commitment to sustainability (Abuzaid et al, 2022), experts revealed that "Waste Management" measure was crucially needed to be included since FM companies take recycling initiatives and waste minimization tactics. To add up, because of the extreme climate conditions in the UAE, the maintenance of infrastructure is critical, underscoring the need for monitoring of air conditioning systems and ensuring the efficient utilization of energy, thus highlighting the importance of measuring "Assets Maintenance Management".…”
Section: Dissecting Performance Measuresmentioning
confidence: 99%
“…The Sustainable City in Dubai, Sharjah, and in the future in Abu Dhabi, focuses on three pillars of sustainability i.e., social, economic, and environmental. EXPO2020 was yet another remarkable undertaking for the world stage, as it was built with sustainability parameters at the forefront and is currently operating in an energy-efficient environment [42]. According to Asif (2016) [43], among all the GCC countries, the UAE has been at the forefront of having the biggest share of green buildings in the Middle East and North Africa (MENA) region.…”
Section: Uae's Climate Adaptation In the Built Environment Sectormentioning
confidence: 99%
“…La tecnología se ha convertido en la herramienta principal para que los clientes se encaminen por obtener un comportamiento sostenible, en otras palabras, esta facilita que los beneficios percibidos en productos ecológicos lleguen a tener un impacto positivo en la conducta sostenible de los consumidores (Nanggong & Rahmatia, 2019). De acuerdo con conceptos globales sobre la sostenibilidad social esta abarca las necesidades de los grupos de la sociedad tales como psicológicas, fisiológicas y de seguridad, con el objeto de abordarlas de forma general (Abuzaid et al, 2022), es considerada una peculiaridad de la sociedad la cual promueve circunstancias perdurables para el bienestar de la humanidad, en especial para grupos de personas en condiciones susceptibles (Ajmal et al, 2018).…”
Section: Sostenibilidad Social Percibidaunclassified